1996
DOI: 10.1111/j.1460-2695.1996.tb01037.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cathodic Protection Potential on Corrosion Fatigue Crack Growth Rate of an Offshore Structural Steel

Abstract: Duplicate tests have been performed to determine the effect of cathodic protection potential on corrosion fatigue crack growth rate of a modern offshore structural steel, produced by thermomechanically controlled processes. The experiments were carried out using compact tension specimens exposed to artificial seawater at 10°C and subjected to constant amplitude loading at 0.35 Hz. Reproducible results showed that the merits of cathodic protection potentials are strongly dependent on stress intensity ratio R an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…It ensues that the fatigue behaviour of these materials is well documented in this environment, which appears consequently as a natural reference. This is the case in many works [1][2][3][4] that have been published on the effects of a saline solution on the Fatigue Crack Growth Rates (FCGRs) of long cracks in structural steels under cathodic protection.…”
Section: Introductionmentioning
confidence: 99%
“…It ensues that the fatigue behaviour of these materials is well documented in this environment, which appears consequently as a natural reference. This is the case in many works [1][2][3][4] that have been published on the effects of a saline solution on the Fatigue Crack Growth Rates (FCGRs) of long cracks in structural steels under cathodic protection.…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of research results have indicated that the CP potential ranging from -800 to -1,100 mV SCE works for the steels in seawater, and the environmental effect on FCP in such conditions is marginal [9,40]. It has also been reported that the environmental effect on FCP in low K regime is negligible as crack extension is dependent on achieving a critical level of crack tip cyclic strain that is independent of environmental condition [22,40,41]. Similarly, mechanical effects dominate and the crack is believed to advance as a faster rate than the diffusion of hydrogen in steel at high values of K [22,36,41].…”
Section: Resultsmentioning
confidence: 97%
“…It has also been reported that the environmental effect on FCP in low K regime is negligible as crack extension is dependent on achieving a critical level of crack tip cyclic strain that is independent of environmental condition [22,40,41]. Similarly, mechanical effects dominate and the crack is believed to advance as a faster rate than the diffusion of hydrogen in steel at high values of K [22,36,41]. In intermediate K regime, the increase in FCP rates for steels in seawater under CP potentials has been reported compared to an air environment, due to the effect of hydrogen within and immediately ahead of the crack tip plastic zone [22,42,43].…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of a particular variable such as R‐ratio with the environmental test condition may also have some influence on crack growth rates. For example, in and , at more negative cathodic potentials, crack growth rates were significantly influenced at higher R‐ratios compared with those obtained under a free corrosion potential. At an R‐ratio of 0, in an aerated 3.5% sodium chloride solution, Kermani and Harrop also found that crack growth in BS4360 50D steel increased at a more negative potential than at free corrosion potential.…”
Section: Introductionmentioning
confidence: 89%
“…(10) are the same as those given by Huang and Moan in Eq. (8). The correction factor can be defined as…”
Section: E a N S T R E S S M O D E L Smentioning
confidence: 99%